Multiple Mechanisms Are Involved in Repression of Filamentous Phage SW1 Transcription by the DNA-Binding Protein FpsR. Issue 6 (15th March 2019) - Jian, Huahua; Xu, Guanpeng; Liu, Shunzhang; Hao, Yali; Meng, Canxing; Xu, Jianrong; Zhang, Yue; Liu, Xipeng; Xiao, Xiang
Abstract: SW1 is the first filamentous phage isolated from a deep-sea environment. Nevertheless, the mechanism by which the SW1 genetic switch is controlled is largely unknown. In this study, the function of the phage-encoded FpsR protein was characterized by molecular biological and biochemical analyses. The deletion of fpsR increased the copy number of SW1 ssDNA and mRNA, indicating that FpsR functions as a repressor. In addition, transcription from the fpsR promoter was shown to be increased in an fpsR deletion mutant, suggesting self-repression by FpsR. Purified FpsR bound to four adjacent operator sites ( O1–O4 ) embedded within the fpsA promoter and the fpsA–fpsR intergenic region. A surface plasmon resonance experiment showed that FpsR can bind to the O1–O4 operators separately and with different binding affinity, and the dissociation constants of FpsR with O2 and O3 were found to be lower at 4 °C than at 20 °C. A gel permeation chromatography assay revealed that FpsR oligomerized to form tetramers. Point mutation analysis indicated that the C-terminal domain influenced the binding affinity and regulatory function of FpsR. Collectively, these data support a model in which FpsR actively regulates phage production by interacting with the corresponding operators, thus playing a crucial role in the SW1 genetic switch. Graphical Abstract: Unlabelled Image Highlights: The mechanism that regulates the genetic switch of benthic phages is unknown. FpsR negatively regulates DNA replication and gene transcription of phage SW1. The C-terminal domain influences the binding affinity and regulatory function of FpsR. Steric hindrance and "Roadblock" mechanisms are involved in the repression by FpsR.